Drug utilization study of co-administration of nonsteroidal anti-inflammatory drugs and gastroprotective agents in an orthopaedics outpatients department of a tertiary care hospital in West Bengal - Kumar, Ajay; Dalai, Chanchal Kumar; Ghosh, Amit Kumar; Ray, Madhumita (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Non steroidal anti-inflammatory drugs (NSAIDs) are the commonly prescribed analgesic in the orthopaedics department. NSAIDs are prescribed for a long period in both acute condition (like fracture of bones, muscle injury, postoperative procedures etc) or chronic conditions (osteoarthritis etc). However, they have many adverse effects, especially gastrointestinal toxicity when use regularly. For this reason NSAIDs are frequently co-prescribed with gastro protective agents. Common gastroprotective agents are proton pump inhibitors (PPI), H2 blockers, sucralfate, antacids and misoprostol (prostaglandin analogue). Methods: A cross-sectional, unicentric drug utilization study was conducted. Prescriptions were collected from patients attending the orthopaedic outpatients department. The prescription pattern of NSAIDs, gastroprotective agents or co-administration of NSAIDS and gastroprotective agents were analyzed. Results: A total of 977 prescriptions were studied; in which 928 prescriptions contained NSAIDs with gastroprotective agents (97.92%). The most common gastroprotective agents combined with NSAIDs was H2 receptor blockers (60.56%), followed by proton pump inhibitors (PPIs) (21.65%), while antacids are prescribed least (17.78%). Misoprostol or sucralfate were not used at all. Conclusions: NSAIDs are commonly co-prescribed with gastroprotective agents in high percentage.